DETERMINE THE POLICY TARGET TO INCREASE INSTITUTIONAL DELIVERY AMONG INDONESIAN FEMALE WORKERS - Isyatun Mardhiyah Syahri; Agung Dwi Laksono; Maya Fitria; Nikmatur Rohmah; Dina Bisara Lolong; Abdulah Saleh Alruwaili (Jurnal Administrasi Kesehatan Indonesia)
Introduction: Indonesia continues to face a significant challenge in terms of maternal and infant mortality. The government is working to promote the use of health facilities for childbirth to mitigate maternal mortality.